Manufacturing Workers: How Adult Literacy and Welfare-to-Work Programs Construct the World of Work - Jennifer A. Sandlin (Adult Education Research Conference, 2001)
This paper examines the complex ways educational programs for welfare recipients construct "success," especially in terms of the workplace. Teachers, students, and curricula in the programs represented success as largely an outcome of individual agency, while also recognizing but minimizing the importance of structural factors.